2018
DOI: 10.1016/j.acap.2018.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Medication Errors With Pediatric Liquid Acetaminophen After Standardization of Concentration and Packaging Improvements

Abstract: Implementation of a single concentration for pediatric liquid acetaminophen products and packaging changes were associated with a decrease in medication errors reported to poison control centers. Medication errors are particularly problematic for children <2 years of age, for whom there are no specific labeled dosing instructions. Improved efforts to provide caregivers with dosing instructions for these children are encouraged.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…10 Although this demonstrates effectiveness with solid dose formulations, similar work is warranted for effectiveness of flow restrictors on liquid prescription medications to prevent AUIs. The data presented here extend those reported by Brass et al, 11 who described a reduction in medication error exposures to pediatric liquid single-ingredient acetaminophen since 2011 following the change to a single pediatric concentration of acetaminophen that coincided with packaging innovation. Although medication errors and AUIs are two distinct and very different reasons for potentially dangerous pediatric exposures, the publication by Brass and colleagues 11 serves as a reminder that other changes to OTC medications have occurred in recent years that could also have contributed to the reduction in acetaminophen AUIs.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…10 Although this demonstrates effectiveness with solid dose formulations, similar work is warranted for effectiveness of flow restrictors on liquid prescription medications to prevent AUIs. The data presented here extend those reported by Brass et al, 11 who described a reduction in medication error exposures to pediatric liquid single-ingredient acetaminophen since 2011 following the change to a single pediatric concentration of acetaminophen that coincided with packaging innovation. Although medication errors and AUIs are two distinct and very different reasons for potentially dangerous pediatric exposures, the publication by Brass and colleagues 11 serves as a reminder that other changes to OTC medications have occurred in recent years that could also have contributed to the reduction in acetaminophen AUIs.…”
Section: Discussionsupporting
confidence: 87%
“…The data presented here extend those reported by Brass et al, 11 who described a reduction in medication error exposures to pediatric liquid single-ingredient acetaminophen since 2011 following the change to a single pediatric concentration of acetaminophen that coincided with packaging innovation. Although medication errors and AUIs are two distinct and very different reasons for potentially dangerous pediatric exposures, the publication by Brass and colleagues 11 serves as a reminder that other changes to OTC medications have occurred in recent years that could also have contributed to the reduction in acetaminophen AUIs. Nonetheless, the volume and severity of exposures prevented suggest that even if a fraction of this reduction was due to flow restrictors, there is a substantial number of acetaminophen AUIs that have been prevented by flow restrictors, and other AUIs might be similarly prevented if flow restrictors are applied to other commonly administered OTC products.…”
Section: Discussionsupporting
confidence: 87%
“…However, our findings are likely informative to stakeholders in other countries given that there is considerable overlap between the ISMP List and lists from other countries. 36-39 Future work should replicate our study using other US and non-US SALA lists. 25,30,36-40…”
Section: Discussionmentioning
confidence: 87%
“…Studies have suggested that changing product packaging or affixing an auxiliary or storage label to differentiate between potentially confusing medications could reduce medication errors. [32][33][34] A review of the medication under approval evaluation and existing products from the same manufacturer may also help prevent SALA confusion. It may also be beneficial for The Joint Commission to consider recommending that health care facilities evaluate SALA medications that share multiple product attributes.…”
Section: Discussionmentioning
confidence: 99%
“…Although the BNFC guidelines were updated in 2011 to include narrower age bands than those listed on the labels of many commonly used over-the-counter products, calculations based on UK-WHO growth charts using these guidelines yielded inappropriate calculated doses for both overweight and underweight children [ 49 ]. One rationale for age- instead of weight-based dosing is that weight-based calculations can be difficult for caregivers [ 50 ], highlighting a significant unmet need for clearer package insert guidelines.…”
Section: Results Of Literature Reviewmentioning
confidence: 99%